Is the exclusion of the complainant in the Disciplinary Administrative Procedure of the National Police of Peru compatible with a Constitutional State of Law? - Gonzales Pastor, Nataly (2025)
Law 30714, enacted in 2017, constitutes the regulatory framework governing the conduct and discipline of members of the Peruvian National Police. This legal instrument establishes guiding principles, protected legal interests, the classification of infractions and disciplinary administrative sanctions, as well as the disciplinary procedure applicable to police personnel.This article analyzes the regulatory design of the police Disciplinary Administrative Procedure from a constitutional perspective, focusing on the exclusion of the complainant as a party to the procedure. It argues that this exclusion deviates from the Constitutional State of Law and violates principles such as the right to defense, due administrative process, and effective judicial protection. Furthermore, it prevents the complainant from accessing the case file, participating in the investigation, or challenging decisions such as the dismissal of their complaint, thus fostering institutional discretion and weakening citizen oversight.In this sense, the text examines this problem in light of constitutional jurisprudence, doctrine and international standards, proposing a legal reform that reconfigures the police disciplinary procedure according to a guarantee-based and transparent model, recognizing the complainant as a party with minimal powers of intervention, in protection of the Constitutional State of Law and public interests.